Consumer involvement, consumer online engagement, and consumer loyalty in airline and hospitality services among generation X and Y - Leong, Mei Kei (2018)
Previous studies had explicitly examined the constructs of consumer involvement, consumer online engagement, and consumer loyalty. However, only few researchers have conducted studies to understand the relationships between these constructs especially across generations. Furthermore, studies on consumer loyalty have become the central focus of various parties as it is the major determinant of market growth and an influencer which affects consumer behaviour. Thus, the main objective of this study was to examine the dimensions of consumer involvement (importance, pleasure, sign, risk consequence, and risk probability) in influencing consumer loyalty among Generation X and Y in airline and hospitality services context. This study also looked at the mediating effect of consumer online engagement (with its dimensions of affective, behaviour, and cognitive engagement) on the relationship between consumer involvement and consumer loyalty. The moderation effect of Generation X and Y was examined in the study to ascertain the differences between the two generations on the relationship between consumer online engagement and consumer loyalty. The conceptual framework was developed based on the reasoned linkage between the variables and the theoretical foundations of the Service Dominant Logic Theory, the Consumer Engagement Model, and the Three H’s Model. Convenience sampling method was used to collect the data of 390 respondents through Facebook. Meanwhile, this research had acquire the desired number of respondents, with an approximately equal number of respondents from Generation X and Generation Y. The self-administrative questionnaires were widely distributed by using an online survey platform known as Survey Monkey. The collected data were statistically analysed by using Statistical Package for the Social Sciences (SPSS) and Smart PLS software. The basic analysis such as descriptive analysis was performed by using SPSS, while the inferential analysis such as Structural Equation Modelling was carried out by using Smart PLS. Based on the findings, it was observed that the level of consumer loyalty portrayed towards the airline and hospitality services among the Generation X and Generation Y were between moderate and high. The results also discovered that there were significant relationships between dimensions of consumer involvement (importance, pleasure, and sign) and consumer loyalty. The dimensions of consumer online engagement (affective and behaviour) were distinguished as the mediator for the relationship between consumer involvement and consumer loyalty. The mediator effect was partially mediated the relationship between consumer online engagement and consumer loyalty. Nonetheless, the cognitive engagement does not display any mediation effect on the relationship between consumer involvement and consumer loyalty. As for the moderator of Generation X and Y, the result displayed significant moderation effect with regards to the consumer online engagement and consumer loyalty relationship. The moderator of Generation X and Y has increased the direct variance explained within the model from 19.5% to 32.3%. This study has contributed to the existing body of knowledge by providing support for the importance of consumer involvement and consumer online engagement towards consumer loyalty, based on theoretical reasoning and empirical findings. The findings of the study have also highlighted some important implications, while some recommendations for future researchers have also been put forward to facilitate the understanding of consumer loyalty.